Obce narody w Księdze Sofoniasza (So 2,4-15) - Stasiak, Sławomir (Collectanea Theologica, 2018)
The oracles against foreign nations in the Book of Zephaniah (Zeph 2:4-15) were directed against the Philistines, the Ammonites, the Moabites, the Egyptians and against the Assyrians. Their order is not quite clear, challenging, and wonder if it is really explicable to the very end. The way the oracle is presented against the Philistines (Zeph 2:4-7) is based on the multitude of names of places, which belonged to this part of Palestine. The words directed against them “I will destroy you until no inhabitant is left” (Zeph 2:5), force the Judeans to reflect on their behavior, which could lead on to their annihilation, the way the foreign nations will be destroyed at this moment. The attrition of the Philistines is to function as a warning for the Judeans against the imminent and awaited punishment, unless they change their conduct. The oracles against the Moabites and the Ammonites (2:8-11) bewilder in two aspects. First of all, the issue concerns the determination of kōl ʼijjê haggôjim (Zeph 2:11), which can either refer to all nations in general, or only to those nations which are hostile towards the Israel. In the direct, preceding context, Zephaniah was writing about the victory of JHWH over pagan gods (v. 11a); Thus, one may suppose that the representatives of even the remotest corners of the earth will pay homage to JHWH. Secondly, what is surprising is the reverse order, the reversal of the usual order in the oracles against the nations, in which the punishment is presented as first and then its justification. Whereas, Zephaniah starts with justification (v. 8 and 10), and later mentions the punishment (v. 9 and 11a). Why was the oracle constructed in this specific way by the prophet? First of all, it may have constituted an emphasis which Zephaniah uses to stress the cause (justification) of the punishment imposed on the Moabites and the Ammonites. However, attention must also be drawn to w. 11b, which contains eschatological announcement of the universal and widespread cult of JHWH. Thus, the expression of the oracle was meant to lead to eschatological proclamation, in an climactic construction. The words directed against Egypt (Zeph 2:12) are so cursory that some scholars regard them as part of the oracle against Assyria. Yet, it seems that such a connection would be completely unjustifiable, merely because of the fact that the punishment the Nubians and the Assyrians will face will be different, not to mention the fact that the empires of Assyria and Egypt were immemorial enemies of Israel, but different, though. The sword taken out against Egypt (Zeph 2:12) undoubtedly, constitutes a kind of glancing reference to the scene which took place at the gates of Jericho, when Joshua encountered the Angel of God with an unsheathed sword (Jos 5:13). The description of extermination and destruction of Assyria (Zeph 2:13-14) is comprehensive and extensive because the oracles against foreign nations in the Book of Zephaniah reach their climax there. Justification in this case seems to be perfunctory, though (v. 15) especially considering the immensity of the punishment.